Students' Perception of Business Incubators In Increasing Interest in Business at Makassar Tourism Polytechnic - Mahmuddin; Halim, Nur; Wisudawaty, Ika (Cita konsultindo, 2025)
This study aims to explore students' perceptions of the Business Incubator at Makassar Tourism Polytechnic in increasing entrepreneurial interest. Using a qualitative approach, data were collected through interviews, observation, and documentation. The results show that most students are aware of the incubator, but their understanding varies. Students actively involved in the program benefit from training, mentoring, and business networking, which foster their entrepreneurial interest. However, challenges such as lack of information, limited time, and fear of failure remain. The business incubator is considered important in shaping students' interest and readiness for entrepreneurship.